Angiolymphoid hyperplasia with eosinophilia developing in a patient with history of peripheral T-cell lymphoma: evidence for multicentric T-cell lymphoproliferative process - Auerbach Aaron; Wang Guanghua; Zhao X Frank; Tavora Fabio; Gonzalez-Cuyar Luis F; Aguilera Nadine; Burke Allen P (BMC, 2008)
Abstract Background Angiolymphoid hyperplasia with eosinophilia (ALHE) is a vasocentric process characterized by infiltrates of lymphocytes and eosinophils, usually affecting the muscular arteries of the head and neck. Currently it is unclear whether it is a reactive or neoplastic process. Report We present a 61-year-old African American male with a twenty year history of superficial skin patches involving the head and neck region. An excisional biopsy of a right submental lymph node revealed an atypical T-cell lymphocytic process, diagnosed as peripheral T-cell lymphoma after immunophenotyping and molecular studies. Three months later the patient underwent a biopsy of a left temporal nodule that was diagnosed as ALHE. Subsequently, at two year follow-up, the patient was diagnosed with Mycosis Fungoides. Polymerase chain reaction for T cell receptor gamma showed the same T-cell receptor gene rearrangement in both the temporal mass and the right submental lymph node. Conclusion ALHE with molecular evidence of monoclonality is extremely unusual, as is the association with nodal peripheral T-cell nodal lymphoma. The findings of this case support our hypothesis that ALHE might be an early form of T-cell lymphoma.